The effect of modulators on lung function following inpatient treatment for CF exacerbations - Stone, Anne; Haag, Meredith B.; Muirhead, Corinne A.; Markwardt, Sheila; MacDonald, Kelvin D. (Frontiers in Pediatrics, 2025)
BackgroundModulator therapy restores CFTR function and has led to health benefits for persons with cystic fibrosis (CF) (PwCF), including lower rates of pulmonary exacerbations. It is unknown if modulators affect lung function trajectories after inpatient treatment of pulmonary exacerbations (PEx).MethodsWe conducted a retrospective review of hospital encounters for PEx for subjects 6–25 years old with mild to moderate lung disease admitted to a large tertiary care center from 2014 to 2021 to capture hospitalizations of PwCF before and after starting modulators. Descriptive analyses were used to characterize the population and lung function findings. Logistic regression analyses were conducted to assess the association between modulators and FEV1pp outcomes.ResultsThe study sample included 575 encounters representing 149 unique PwCF. Hospital encounters of PwCF taking modulator were associated with higher mean FEV1pp at baseline, midway, discharge, and follow-up assessments. Mean FEV1pp increased during inpatient treatment of PEx with loss of lung function at follow-up, regardless of modulator use. Hospital encounters of PwCF not taking modulators were associated with less significant improvements in mean FEV1pp from admission at both midway and discharge (15.6% vs. 18.3%, 19.9% vs. 22.5%, no modulator vs. modulator groups, respectively). At follow-up, hospitalizations of PwCF taking modulators were associated with a significantly higher probability of sustained improvement in FEV1pp from discharge (difference in probabilities 0.119, p < 0.05) and a lower probability of loss of lung function from baseline (difference in probabilities −0.123, p < 0.05).ConclusionsHospitalizations for PwCF taking modulators were associated with higher lung function at all assessments. Hospitalizations of PwCF taking modulators were associated with a significantly higher probability of sustained improvement in FEV1pp following discharge and a lower probability of loss of lung function from baseline.